2004
DOI: 10.1074/jbc.m406055200
|View full text |Cite
|
Sign up to set email alerts
|

The role of the length and sequence of the linker domain of cytochrome b5 in stimulating cytochrome P450 2B4 catalysis.

Abstract: Cytochrome b 5 (cyt b 5 ) is a 15-kDa amphipathic protein with a cytosolic amino-terminal catalytic heme domain, which is anchored to the microsomal membrane by a hydrophobic transmembrane ␣-helix at its carboxyl terminus. These two domains are connected by an ϳ15-amino acid linker domain, Ser 90 -Asp 104 , which has been modified by site-directed mutagenesis to investigate whether the length or sequence of the linker influences the ability of cyt b 5 to bind ferric cytochrome P450 2B4 and donate an electron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 37 publications
(74 reference statements)
3
38
0
Order By: Relevance
“…2B). The inability of the soluble haem core to stimulate the lyase activity is in agreement with other reconstituted CYP-CPR-cytochrome b 5 studies, indicating that the membrane-anchoring region provides not only correct membrane-integrated topology of cytochrome b 5 for maximal interaction with CYP17 but also facilitates protein-protein association through charge-based pairings (Lamb et al 2001, Clarke et al 2004. Moreover, Mulrooney et al (2004) have recently provided evidence that the hydrophobic interactions of the membraneanchoring regions occur via non-specific interactions.…”
Section: Allosteric Role Of Cytochrome B 5 In Cyp17 Catalysissupporting
confidence: 87%
See 1 more Smart Citation
“…2B). The inability of the soluble haem core to stimulate the lyase activity is in agreement with other reconstituted CYP-CPR-cytochrome b 5 studies, indicating that the membrane-anchoring region provides not only correct membrane-integrated topology of cytochrome b 5 for maximal interaction with CYP17 but also facilitates protein-protein association through charge-based pairings (Lamb et al 2001, Clarke et al 2004. Moreover, Mulrooney et al (2004) have recently provided evidence that the hydrophobic interactions of the membraneanchoring regions occur via non-specific interactions.…”
Section: Allosteric Role Of Cytochrome B 5 In Cyp17 Catalysissupporting
confidence: 87%
“…There have been relatively few studies on cytochrome b 5 mutagenesis regarding its influence on CYP catalysis (Chudaev et al 2001, Clarke et al 2004 and as yet there have been no reports on the effect of cytochrome b 5 mutagenesis on the steroidal activity of CYP17. Earlier work by Usanov's group (Usanov & Chashchin 1991) showed that substitution of the residue Glu 42 with Lys on cytochrome b 5 resulted in reduction of the cholesterol side-chain cleavage activity of CYP11 by almost 40%, suggesting that the anionic residue of cytochrome b 5 was important for electrostatic interaction with CYP11.…”
Section: Future Prospectsmentioning
confidence: 99%
“…The changes in the profiles of regioisomer formation from phenyldiazene suggest that in S119W (BЈ-C loop), active site topology is altered upon b 5 -interaction (Yamaguchi et al, 2003). In this context it is important to note that some basic amino acid residues in the C and CЈ helix are thought to be involved in binding between P450 2B4 and b 5 (Bridges et al, 1998;Clarke et al, 2004). Likewise, the substitutions at Ile-301 and Ala-305 in the SRS-4 region, which is closest to the heme (Williams et al, 2004;Yano et al, 2004), with larger side chains may cause a structural transition leading to impaired b 5 -interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Activity of cytP4502B4 in Solution and Bicelles, Methoxyflurane-The metabolism of the anesthetic, methoxyflurane (C 3 H 4 Cl 2 F 2 O), by cytP4502B4 was measured in a reconstituted aqueous system with and without cytb 5 (23). The activity of cytP450 was also measured in bicelles in the presence and absence of cytb 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, although the interaction of cytb 5 with various membranes has been previously studied (20 -22), the structure of membrane-bound cytb 5 is lacking. However, only the full-length membrane-binding form of microsomal cytb 5 influences the enzymatic activity of cytP450 (23,24); truncated cytb 5 is only capable of electron transfer to water-soluble oxidative enzymes (e.g. cytochrome c and metmyoglobin) (25).…”
Section: (16 Kda) Incorporated In Two Different Membrane Mimetics (Dmentioning
confidence: 99%